BOOK REVIEW: «INFINITE POWERS. HOW CALCULUS REVEALS THE SECRETS OF THE UNIVERSE» - Dieorditsa, Taiana; Tolmachov, Volodimir (Physical and Mathematical Education, 2023)
In this book, Professor S. Strogatz explains the fundamental ideas of calculus, highlights the history of the emergence of these ideas, and demonstrates their impact on the development of science and technology. He addresses thoughtful, curious, knowledgeable people with little background in advanced math. This book will help them a better feeling for what calculus is all about and why it’s so enthralling to those who get it. The book's leitmotiv is an aphorism formulated bya famous physicist, R. Feynman: calculus is the language God talks. «Infinite Powers» is worth reading to discover calculus as a part of the culture.
Keywords: mathematics; calculus; infinity; differential equations; culture